(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Some lesions in the brain are difficult to approach through a single common route / trajectory. For those, dual approach combined together may ensure easier safe removal with better outcome as we had lesions like left petroclival meningioma & large craniopharyngioma. Methods Two patients, one left petroclival meningioma and one suprasellar craniopharyngioma with intraventricular extension underwent surgery with dual approach at the Neurosurgery department, BSMMU. After detailed clinical and radiological evaluation, the left petroclival meningioma patient was planned for a combined pre and post sigmoid petrosectomy and retromastoid retrosigmoid route. These were accomplished in two stages, three months apart. The craniopharyngioma patient with intraventricular extension underwent surgery through pterional transsylvian and frontal anterior trans-callosal approach in a single sitting. Bang. J Neurosurgery 2020; 10(1): 111-118